La renovación pedagógica en el currículo por problemas (2021)
The aim of the present essay is to analyze the different changes in the pedagogical and curricular thought, which has been caused by the transformations in the social conditions, due to the new epistemological and technological orientations, and especially because of the new approaches that have located the human being as the center of the educative project. This proposed conceptual approach, intends the understanding of the new educative dynamics and the new role in the interaction process between the teacher and the student, and the teaching-learning system, which justify and motivate the design of a methodological and curricular system at the Universidad Católica Popular del Risaralda, based on a problematic curriculum and the academic work of lecturers committee.